Translational medicine: the risk of failure in delay and how to reduce it - Wehling, Martin (Henry Stewart Talks, 2022)
Translational medicine, Biomarker development, Risk assessment, Risk estimator, Scoring system, Structured approach, Clinical pharmacology, Interdisciplinary cooperation